Genetic resilience in chickens against bacterial, viral and protozoal pathogens - Gul, Haji; Habib, Gul; Khan, Ibrar Muhammad; Rahman, Sajid Ur; Khan, Nazir Muhammad; Wang, Hongcheng; Khan, Najeeb Ullah; Liu, Yong (Frontiers in Veterinary Science, 2022)
Genome makes an individual breed unique with distinctive characteristics that pass from one generation to the next. The allelic heterogeneity of a certain breed gives a different response to a pathogen with different genomic expressions. Disease resistance in chicken is a polygenic trait, which deals with different genes that confer the resistance against pathogens; encompassing major histocompatibility (MHC) molecules, immunoglobulins, cytokines, interleukins, T and B cells, and subsets CD4+ and CD8+ T lymphocytes, thus involved in protection of the host. The MHC is associated with antigen presentation, antibody production, and cytokines stimulation, which elaborates the role in disease resistance. The natural resistance-associated macrophage protein 1 (Nramp-1), interferon (IFN), myxovirus-resistance gene, myeloid differentiation primary response 88 (MyD88), receptor-interacting serine/threonine kinase 2 (RIP2), and heterophile cells are involved in disease resistance and susceptibility of chicken. The studies of disease resistance genetics, epigenetics and quantitative trait loci would ease the identification of resistance markers and the development of disease resistance breeds. It is apparent that microbial infections are responsible for significant outbreaks and blighted the poultry industry. Breeding chickens with disease-resistant strains may helpful in tackling the pathogens, and also increasing understanding of host genetics in fight against communicable diseases. The advanced technologies such as CRISPR/Cas9 system, whole genome sequencing, RNA sequencing, and high-density single nucleotide polymorphism (SNP) genotyping are assisting in the development of resistant breeds. It would significantly decrease the use of antibiotics and vaccination in poultry. In this review, we have illuminated the recent genetic basis of infection and genomic modification that increase resistance against a variety of pathogens in chickens.